2012
DOI: 10.1128/jvi.06266-11
|View full text |Cite
|
Sign up to set email alerts
|

Role of β-Catenin and TCF/LEF Family Members in Transcriptional Activity of HIV in Astrocytes

Abstract: The Wnt/␤-catenin pathway is involved in diverse cell functions governing development and disease. ␤-Catenin, a central mediator of this pathway, binds to members of the TCF/LEF family of transcription factors to modulate hundreds of genes. Active Wnt/␤-catenin/TCF-4 signaling plays a significant role in repression of HIV-1 replication in multiple cell targets, including astrocytes. To determine the mechanism by which active ␤-catenin/TCF-4 leads to inhibition of HIV replication, we knocked down ␤-catenin or T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
102
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 44 publications
(60 reference statements)
0
102
0
Order By: Relevance
“…TCF family members have been recently reported to inhibit HIV type 1 (HIV-1) basal transcription (17). Therefore, we analyzed effects of TCF1 and LEF1 on transcription from the HTLV-1 LTR.…”
Section: Resultsmentioning
confidence: 99%
“…TCF family members have been recently reported to inhibit HIV type 1 (HIV-1) basal transcription (17). Therefore, we analyzed effects of TCF1 and LEF1 on transcription from the HTLV-1 LTR.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro, astrocytes support low-level HIV replication, which is inducible in response to proinflammatory signals (11)(12)(13). Through a series of publications, we also demonstrated that robust/productive HIV replication in astrocytes is restricted but can be supported under inflammatory signals, such as gamma interferon (IFN-␥) (13)(14)(15)(16)(17). Priming astrocytes with IFN-␥, in particular, facilitates HIV replication in astrocytes (13)(14)(15)(16)(17).…”
mentioning
confidence: 91%
“…Through a series of publications, we also demonstrated that robust/productive HIV replication in astrocytes is restricted but can be supported under inflammatory signals, such as gamma interferon (IFN-␥) (13)(14)(15)(16)(17). Priming astrocytes with IFN-␥, in particular, facilitates HIV replication in astrocytes (13)(14)(15)(16)(17). We used primary human progenitor-derived astrocytes (PDAs) and two astrocytoma cell lines (U87MG and U138) in this study to define the role of astrocytes in HIV latency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These transcriptional factors negatively regulate the HIV LTR by recruiting histone deacetylases (HDACs) and methyltransferases to alter the chromatin structure to render it inaccessible to the transcriptional machinery and hence play a significant role in repression of HIV transcription. We and others have identified an additional transcriptional factor (T cell factor 4 ) that inhibits HIV replication (3,26,28,38). The mechanism by which TCF-4 mediates HIV repression is not entirely clear and is the focus of this study.…”
mentioning
confidence: 96%